Deep ocean - Rice, A. L. (Washington, DC : Smithsonian Institution Press, 2000)
This lively and informative book tells how oceanography developed as a science and summarizes what is known about organisms that live in the deep ocean. The author is a deep-sea biologist for the British Natural Environment Research Council.
Introducing the ocean -- Development of oceanography -- Vertical life zones in the ocen -- Pastures of the sea -- Mid-water world -- from twilight sone to abyss -- Biodiversity in the deep ocean -- Life on the deep-sea floor -- Monsters of the deep -- Hydrothermal vents -- Man and the deep ocean.
Includes bibliographical references : pages 96 and index.
Keywords: Ocean; Oceanography